Left in the West : literature, culture, and progressive politics in the American West - Woods, Gioia, 1968- (Reno : University of Nevada Press, 2018)
"Left in the West is an edited collection bringing together histories, biographies, close readings, and theories about the literary and cultural left in the American West, especially as it is distinct from the more often-theorized literary left in New York and major eastern metropolitan centers. The collection argues for a new understanding of the relationship between region, progressive political engagement, and literary and cultural work; Woods and her contributors examine the West as a unique socio-political region shaped by specific environmental, social, economic, and ethnic concerns. While the literary left in the West shared many interests with other regional expressions of "left," including labor, class, anti-fascism, and anti-imperialism, the influence of Manifest Destiny and the distinct history of settler colonialism in western territories caused western leftists to develop concerns unique to the region, elevating issues of industrialization and environmental degradation, Native American sovereignty, and immigrant communities' access to power. And as this collection of essays makes clear, western leftists were (and are) deploying a broad range of literary genres and cultural techniques to address these unique concerns"--Provided by publisher.
Part III: Left in Transit: Success and Limitations11. New Bohemias, California Style: The Intimate and Global Networks of Photographic Modernism; 12. "Backward in Time and Forward in Dream of Unknown Memory": Deborah Miranda's Unsettling Colonial Genealogies; 13. Leaving the West for the Left: Louise Thompson Patterson, the New Negro Movement, and Black Women's Activism; 14. Charlotte Perkins Gilman's Herland, Race, and the California Suffrage and Women's Club Movements, 1896-1911; Acknowledgments; Contributors; Index; About the Editor
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on January 08, 2019).
eBooks on EBSCOhost
Keywords: Politics and literature -- West (U.S.) -- History; Right and left (Political science) in literature; LITERARY CRITICISM -- American -- General; Politics and literature; Right and left (Political science) in literature; West United States; Electronic books; History